On Approach for Analysis of Distribution of Temperature During Effects of Radiation on Biological Tissues - Evgeny Leonidovich Pankratov, (Indian Journal of Advanced Mathematics (IJAM), 2026)
Different types of irradiation take essential role in biological processes directly related to human health. Currently they are widely using in clinical practice. In this situation one can find several works to determine therapeutic effects, which were obtained by actions of the irradiation on living organisms. One type of irradiation of tissues of the considered organisms is electromagnetic radiation. A consequence of the radiation tissues of organisms is their heating. In this paper we introduce a model and an analytical approach to analyze distribution of temperature at effect of radiation on biological tissues. We consider a possibility to control of heat transport in biological tissues by choosing of conditions of heating. Also we present an analytical approach for analysis of the obtained model. The approach takes into account changing of parameters of the considered processes on coordinate and time as well as their nonlinearity.